Experimental and Theoretical Study Into On Bottom Stability of Submarine Pipeline under Wave and Currents - Azam Shauqi Bin Abdul Halim, Azam Shauqi (Universiti Teknologi Petronas, 2009)
Pipelines are one of the methods that widely used in oil and gas industries to transport their products as it is economically efficient. Besides that,it is also proven that submarine pipeline is friendly towards the environment as it only contributer 2 percent from total oil spills in the ocean. As it is name,submarine pipeline is lay under the ocean which are hostile environment towards us. Continously exposed to the environment load such and wave currents,these pipelines need to be stable so that it won't get fatigue due to constant movement. Therefore,as on Bottom Stability is vital towards submarine pipeline,this project is concentration on the experimental study to measure the force acting on the model pipeline